Automatic Air Quality Detection System Design in the Industrial Area - Atika Windra Sari; Elvinda Bendra Agustina; Isnaini Almaulida Umami; Yusril Ihza Tachriri; Jessika Artamevira; Elly Safitri (Techno.Com, 2026)
The industrial sector is an essential component of the economic structure. A large number of current enterprises degrade air quality in the environment as a result of chemical exposure. As a result, an air quality detection system was designed with the purpose of monitoring air pollutant levels, temperature, and humidity. The system is immediately integrated with smartphones via the Internet of Things. Carbon dioxide (CO2) and carbon monoxide (CO) levels are measured using a MQ-135 sensor. Temperature and humidity are measured using DHT-11 sensors. The complete system is controlled by a NodeMCU ESP8266 connected to an Arduino. Data was collected from two industries using an IoT-based system for a continuous 24-hour cycle over seven days to capture real-time daily fluctuation trends. The continuous 7-day monitoring reveals a clear daily fluctuation trend synchronized with factory shifts, peaking between 12:00 and 14:00 WIB. Dutatex exhibits a higher pollutant load (peak CO2: 820–850 ppm; CO: 8–9 ppm) than Bimatex (peak CO2: 620–650 ppm; CO: 5–6 ppm), while both facilities successfully maintain peak temperatures below 33.0°C. These empirical results demonstrate that continuous 24-hour data acquisition provides a highly accurate and comprehensive assessment for monitoring industrial air quality and occupational health.   Keywords - Air Quality, NodeMCU ESP8266, IoT, MQ-135, Arduino.